2008
DOI: 10.1007/s11695-007-9393-7
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Intake and Metabolic Bone Disease after Eight Years of Roux-en-Y Gastric Bypass

Abstract: These data suggest that metabolic bone disease could be a complication of this type of surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
1
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 25 publications
2
24
1
4
Order By: Relevance
“…In accordance with other reports (5-12,30), hypercalciuria was not a frequent finding in this sample of post-BS patients. The lack of hypercalciuria may be ascribed to low protein, calcium, and salt intake, which is usually found in this population (14,15,31,32) and was detected in our patient cohort as well. It may also have occurred because calcium supplements were withdrawn 3 days before urine collection in our study.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…In accordance with other reports (5-12,30), hypercalciuria was not a frequent finding in this sample of post-BS patients. The lack of hypercalciuria may be ascribed to low protein, calcium, and salt intake, which is usually found in this population (14,15,31,32) and was detected in our patient cohort as well. It may also have occurred because calcium supplements were withdrawn 3 days before urine collection in our study.…”
Section: Discussionsupporting
confidence: 71%
“…The potential underlying mechanisms for hyperoxaluria have not yet been determined, but some degree of fat malabsorption is speculated to play a role through the binding of fatty acids to calcium, thereby inhibiting the formation of poorly soluble, nonabsorbable calcium oxalate in the intestinal lumen (11,13). Similarly, less calcium in the intestinal lumen as a result of lower dietary calcium intake after surgery (2,14,15) may also reduce these poorly soluble compounds, resulting in more free oxalate available for absorption and thereby increasing urinary oxalate. Increased net intestinal absorption of oxalate due to dysfunction of the anion exchanger SLC26A6, which acts as an oxalate secretor in the small bowel (16), warrants investigation.…”
Section: Introductionmentioning
confidence: 99%
“…(19). A frequência de deficiência de 25OHD relatada nos estudos oscilou de 50% a 80% (20,22,23). As baixas concentrações de 25OHD em pacientes submetidos à DGYR podem ocorrer por sequestro no tecido adiposo, redução na hidroxilação da pré-vitamina devido à esteatose hepática, menor exposição ao sol pelo sedentarismo ou secundária à inflamação que acompanha a obesidade (12,24).…”
Section: Discussionunclassified
“…One study found that 8 years after RYGB although the vast majority showed a strong inverse correlation between vitamin D and PTH, 10% of patients had a vitamin D deficiency with normal PTH. They posed that whilst the vitamin D deficiency was due to malabsorption, the normalisation of PTH was "more intense in the first years" and would eventually resolve [14].…”
Section: Discussionmentioning
confidence: 99%
“…Up to 60-90% of the obese are known to have vitamin D deficiency, even without surgery [11,12] and an inverse correlation between serum vitamin D levels and obesity has been documented [13,14]. Despite this, the deficiency does not seem to translate to clinically relevant consequences such as osteoporosis.…”
Section: Inadequate Intake Of Vitamin D and Calciummentioning
confidence: 99%